Preparation of an eco‐friendly carbon–silicon dual‐phase rubber filler with humic acid and silica sol. Issue 16 (1st December 2021) - Yang, Shicheng; Tan, Jinlong; Xue, Xiaoxiao; Zhang, Yulong; Sun, Qi
Abstract: A new type of carbon–silicon dual‐phase filler (CSDPF) was prepared from highly active and widely available humic acid and low‐cost silica sol as raw materials, which were further used for styrene butadiene rubber (SBR) by ball milling and carbonization methods. The effects of the silica sol content and the bis(3‐triethoxysilylpropyl) tetrasulfide (TESPT) on the structure and surface properties of the CSDPF were investigated systematically. Silica sol combined with humic acid in the carbon–silicon dual‐phase complexes in the form of SiOC, while the TESPT and carbon–silicon dual‐phase complexes were combined in the form of SiOSi in the CSDPF. As the content of silica sol increased in the dual‐phase complexes, the amount and particle size of silica on the surface of CSDPF increased. A certain amount of silica in the fabricated filler facilitated its subsequent modification and applications. Compared with CB/SBR (SBR filled with carbon black 660), the mechanical properties, thermal stability, wear resistance, and wet skid resistance of SBR filled with the CSDPF were significantly improved. This work provides a new strategy for developing CSDPF. Abstract :